A review of ablative techniques in the treatment of breast fibroadenomata. Issue 1 (December 2016) - Peek, Mirjam; Ahmed, Muneer; Pinder, Sarah; Douek, Michael
Abstract Introduction Breast fibroadenomata (FAD) are benign lesions which occur in about 10 % of all women. Diagnosis is made by triple assessment (physical examination, imaging and/or histopathology/cytology). For a definitive diagnosis of FAD, the treatment is conservative unless the patient is symptomatic. For symptomatic patients, the lumps can be surgically excised or removed interventionally by vacuum-assisted mammotomy (VAM). Ablative techniques like high-intensity focused ultrasound (HIFU), cryo-ablation and laser ablation have also been used for the treatment of FAD, providing a minimally invasive treatment without scarring or poor cosmesis. This review summarises current trials using minimally invasive ablative techniques in the treatment of breast FAD. Methods A comprehensive review of studies using minimally invasive ablative techniques was performed. Results There are currently several trials completed or recruiting patients using HIFU, cryo-ablation and laser ablation in the treatment of breast FAD. The results look very promising but cannot be compared at this point due to heterogeneity between studies. Conclusion Minimally invasive ablative techniques like HIFU, cryo-ablation and laser ablation are promising in the treatment of breast FAD. Future trials should be randomised and contain larger numbers of patients to determine the effectiveness of ablative techniques with more precision.